The effect of water-soluble tomato concentrate on elevated serum cholesterol in the middle-aged and elderly Chinese individuals - Yu, Yingxiang; Wu, Yifan; Xie, Lan; Chang, Cuiqing (Frontiers in Nutrition, 2024)
Water-soluble tomato concentrate (WSTC) has been shown to be beneficial for blood flow in healthy populations. A prospective, randomized, double-blind, placebo-controlled clinical trial was conducted to explore the impact of WSTC on populations with elevated cholesterol levels. Sixty individuals aged 35-65 with high cholesterol were enrolled and equally divided into a treatment group (FFG) and a placebo group (PCG). The trial lasted 60 days, divided into a 45-day treatment phase followed by a 15-day observational follow-up. Participants in the FFG received 300mg daily of Fruitflow tablets, while those in the PCG were given placebos. The study showed that there were no significant differences in baseline parameters between the FFG and PCG (P > 0.05). Analysis of platelet aggregation and activation rates post-intervention revealed no significant changes within or between the groups(P > 0.05). Notably, systolic blood pressure (SBP) and diastolic blood pressure (DBP) in the FFG group decreased significantly post-intervention by 4.2% (SBP, P < 0.001) and 3.8% (DBP, P = 0.015), respectively, demonstrating a significant difference compared to the PCG (P = 0.041). These reductions in blood pressure were maintained during the follow-up period. Conversely, the PCG showed no significant changes in SBP and DBP throughout the study period (P > 0.05). Stratified analysis, considering hypertension status, indicated a significant reduction in SBP in the FFG, including both hypertensive and non-hypertensive subjects (P < 0.05), with a trend towards DBP reduction. No significant changes were observed in SBP and DBP in the PCG. Post-intervention, the FFG group showed a significant increase in high-density lipoprotein (HDL) cholesterol (P < 0.05), along with a marked reduction in both weight and body mass index (BMI) (P < 0.05). Furthermore, levels of homocysteine, high-sensitivity C-reactive protein, and fasting blood glucose in the FFG group decreased to lower levels than those in the PCG (P < 0.05). Therefore, WSTC may not affect platelet function in individuals with elevated cholesterol but significantly decreases blood pressure and enhances cardiovascular risk profiles. These findings advocate for WSTC as a viable non-pharmacological option to improve cardiovascular health in hypercholesterolemic individuals, warranting further exploration.Clinical trial registration: https://www.chictr.org.cn/showproj.html?proj=27052, identifier ChiCTR1800015904.